2019
DOI: 10.1039/c9cy02006c
|View full text |Cite
|
Sign up to set email alerts
|

On the active site for electrocatalytic water splitting on late transition metals embedded in graphene

Abstract: Transition-metal atoms embedded in nitrogen-doped graphene can be used for electrocatalytic water splitting, but there are open questions regarding the identity of the active site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…This shift does not improve the agreement between computational and experimental ORR onset potentials: while experimental onset potentials of 0.87 and 0.85 V RHE have been reported for Cu 38 and Pt 39 singleatom catalysts, respectively, both computational models predict negligible ORR activity for the late transition metals at these potentials. However, metal atoms embedded in partially N-substituted double vacancies bind oxygen more strongly than the fully N-substituted sites examined in our study, 11,21 thereby shifting the late transition metals closer to the peak of the volcano. It is therefore important to keep in mind that the catalytic activity depends on the identity of the transition metal atom and its coordination environment.…”
Section: ■ Results and Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This shift does not improve the agreement between computational and experimental ORR onset potentials: while experimental onset potentials of 0.87 and 0.85 V RHE have been reported for Cu 38 and Pt 39 singleatom catalysts, respectively, both computational models predict negligible ORR activity for the late transition metals at these potentials. However, metal atoms embedded in partially N-substituted double vacancies bind oxygen more strongly than the fully N-substituted sites examined in our study, 11,21 thereby shifting the late transition metals closer to the peak of the volcano. It is therefore important to keep in mind that the catalytic activity depends on the identity of the transition metal atom and its coordination environment.…”
Section: ■ Results and Discussionmentioning
confidence: 53%
“…ORR onset potentials from thermodynamic analysis in ref (black squares; linear fit shown as black line) and from microkinetic analysis (red and blue circles for M clean and M O 2 ‑ast , respectively; lines refer to values obtained using linear scaling relations shown in the Supporting Information). Differences in the onset potentials predicted from thermodynamic and microkinetic analysis (Δ U ORR = U ORR mk – U ORR td ) are shown above: positive (negative) values correspond to an increase (decrease) in onset potential due to the microkinetic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to explain the effect of N defects in Ni@CN x we propose an alternative model where Ni adatoms form under reaction conditions. Remarkably, our previous studies demonstrated that N -doping in graphene stabilizes single-metal atom catalysts with increased activity toward water splitting and CO oxidation ( 47 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the slopes of the relationships of Δ G 1 versus Δ G *OH , Δ G 2 versus Δ G *OH , and Δ G 3 versus Δ G *OH are positive, while the slope of Δ G 4 versus Δ G *OH is negative (see Figure d), the ORR activity can be determined by the binding strength of *OH on the different adsorbed sites. Thus, excellent candidates for ORR catalysts should possess an applicable *OH binding strength between −1.0 and 1.5 eV, indicating selectivity toward H 2 O when Δ G *OH is < –0.34 eV . As shown in Figure a, the first hydrogenated step (O 2 + H + + e – → OOH*, Δ G 1 ) and the fourth hydrogenated step (*OH + H + + e – → *H 2 O) determine the RDSs of the entire reduction process corresponding to the ORR and OER mechanisms, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%